2008
DOI: 10.1097/gim.0b013e31817d2ef1
|View full text |Cite
|
Sign up to set email alerts
|

SLC26A4 c.919-2A>G varies among Chinese ethnic groups as a cause of hearing loss

Abstract: Purpose: Mutations in the SLC26A4 gene are second only to GJB2 mutations as a currently identifiable genetic cause of sensorineural hearing loss. In most areas of China, genetic testing for sensorineural hearing loss is unavailable because of limited knowledge of the mutation spectrum. Although SLC26A4 c.919-2AϾG (IVS7-2AϾG) is a common mutation among some Asian populations, the mutation prevalence among various ethnic groups within China has not been studied. Methods: DNA specimens from 3271 subjects with mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
59
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(70 citation statements)
references
References 25 publications
(23 reference statements)
7
59
4
Order By: Relevance
“…In subjects with HL in the present study, the 235delC in the GJB2 gene and c.919-2A N G in the SLC26A4 gene were the most common mutations. This prevalence has also been reported by other studies in Chinese population [20,21]. We found that mutations in GJB2 were detected in 42.0% (68/162) of all subjects, whereas the carrier rate of mutations in the SLC26A4 gene was 21.0% (34/162).…”
Section: Discussionsupporting
confidence: 81%
“…In subjects with HL in the present study, the 235delC in the GJB2 gene and c.919-2A N G in the SLC26A4 gene were the most common mutations. This prevalence has also been reported by other studies in Chinese population [20,21]. We found that mutations in GJB2 were detected in 42.0% (68/162) of all subjects, whereas the carrier rate of mutations in the SLC26A4 gene was 21.0% (34/162).…”
Section: Discussionsupporting
confidence: 81%
“…8,10,11 p.T416P and IVS8+1G4A are common in Northern Europe, whereas p.H723R and IVS7-2A4G are the most common in East Asia. 8,11,12 We earlier identified mutant alleles of SLC26A4 in 10 (4.7%; 95% CI: 2.6-8.4%) of 212 Pakistani families segregating recessive deafness, which were ascertained through the National Centre of Excellence in Molecular Biology (NCEMB) in Pakistan. 8 p.S90L was the most commonly detected mutation in that initial study.…”
Section: Introductionmentioning
confidence: 99%
“…Usami et al (1999) showed that the PDS gene was also responsible for large vestibular aqueduct syndrome (LVAS). There are about 140 types of PDS mutations discovered among patients with PDS or LAVS, with IVS7-2A > G and p.H723R being the most common among East Asia populations (Dai et al, 2008;Pare et al, 2005).…”
Section: Pds (Slc26a4) Gene-related Deafnessmentioning
confidence: 99%